CULTIVATING PATRIOTISM AMONG UNIVERSITY STUDENTS: FACILITATING THE FORMATION OF THE MALAYSIAN FAMILY CONCEPT IN A MULTIRACIAL SOCIETY - Irma Wani Othman; Yusten Karulus; Mohd Nasrun Mohd Talib; Saifulazry Mokhtar; Muhammad Safuan Yusoff; Hidayah Iwani Mohd Kamal (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The concept of patriotic university students is dissected in this writing through four main issues, namely 1) Internalizing the National Principles among students, 2) The role of students in shaping the Malaysian Family Concept through the development of human capital, 3) Strengthening harmony and unity among students across diverse ethnicities, and 4) The formation of a high sense of identity among students. The discussion focuses on (i) the internalization of the National Principles among students, revealing the optimal level of understanding and practice of the National Principles among the younger generation, (ii) strengthening harmony and unity among students across various ethnicities, demonstrating a tolerant attitude among different language and cultural groups, (iii) the enhancement of unity among students of various ethnic backgrounds, realizing the goal of unity for the future harmony of the nation, and (iv) the existence of tolerance values in students proving their identity as patriotic students. The directions and suggestions encompass (a) the critical role of individuals in realizing that the National Principles should be the guiding principles of citizens with a national spirit, (b) the need for the younger generation to emphasize the practice of togetherness among various ethnicities to maintain national unity, (c) the construction of identity through education and knowledge should be the focus of the youth, where the youth play a significant role in nation-building, and (4) to nurture unity values, referring to the fourth issue is through the role of individualism in students themselves by actively participating in unity-oriented programs. In conclusion, patriotic university students can be shaped through the four discussed issues to ensure the formation of students with a national spirit capable of defending the sovereignty and grandeur of the country.